2019
DOI: 10.1007/s10661-019-7226-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological water quality assessment in the degraded Mutara rangelands, northeastern Rwanda

Abstract: Rwanda is a heavily overpopulated country that also suffers from overstocking with livestock, especially following the return of war refuges after the civil war (1991–1995). At present, approximately 20% of the human population in Nyagatare District in northeastern Rwanda has no access to clean drinking water and sanitation. We used a biotic index based on the presence of selected families of aquatic macroinvertebrates, derived from the “Tanzania River Scoring System” (TARISS), to assess water quality at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…The presence of livestock and wildlife and trade movements across countries, could have contributed to the introduction of PPR in north and west parts of Rwanda. Last but not least, Rwanda has experienced large movements of returning citizens from neighboring countries in 1994 and from Tanzania in 2007 as well as Burundian refugees in 2015 (46)(47)(48). These movements of people and their livestock could have contributed to the introduction of PPR in various regions of Rwanda.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of livestock and wildlife and trade movements across countries, could have contributed to the introduction of PPR in north and west parts of Rwanda. Last but not least, Rwanda has experienced large movements of returning citizens from neighboring countries in 1994 and from Tanzania in 2007 as well as Burundian refugees in 2015 (46)(47)(48). These movements of people and their livestock could have contributed to the introduction of PPR in various regions of Rwanda.…”
Section: Discussionmentioning
confidence: 99%
“…This led to a sharp increase in human population density (483.1 individuals/km 2 ; NISR, 2014) and severe overstocking with cattle (64.9 individuals/km 2 ; Wronski et al, 2017). Further details on the history, ecology and hydrography of our study area can be found in Dusabe et al (2019). ], and presence/absence of macrophytes.…”
Section: Study Area and Assessment Of Fish Communitiesmentioning
confidence: 99%
“…Our present study tested the generality of this pattern, but this time focusing on a paleotropical stream ecosystem in the upper Nile drainage (Swain, 2011). Streams in the heavily overpopulated and overstocked Mutara rangelands in northeastern Rwanda receive pollution chiefly from domestic wastewater and cattle dung (Dusabe et al, 2019). At the same time, the human population of Nyagatare district is critically dependent on clean surface water as a source of drinking water (Ministry of Infrastructure, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been adapted for non-wadeable, deltaic aquatic biotopes in the Okavango Delta in Botswana: Okavango Assessment System (OKASS; Dallas, 2009). TARISS has been used in Ugandan and Rwandan rivers to assess water quality (Dusabe et al, 2019;Tumusiime et al, 2019), although identifications of macroinvertebrates were done on preserved samples in the laboratory and not in the field, and in the case of Dusabe et al (2019), the TARISS sampling protocol was not followed as biotopes were combined.…”
Section: Introductionmentioning
confidence: 99%